2014
DOI: 10.1111/mmi.12893
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalispCF10‐encoded surface proteins PrgA, PrgB (aggregation substance) and PrgC contribute to plasmid transfer, biofilm formation and virulence

Abstract: SUMMARY Enterococcus faecalis pCF10 transfers at high frequencies upon pheromone induction of the prgQ transfer operon. This operon codes for three cell-wall-anchored proteins - PrgA, PrgB (aggregation substance), and PrgC - and a type IV secretion system through which the plasmid is delivered to recipient cells. Here, we defined the contributions of the Prg surface proteins to plasmid transfer, biofilm formation, and virulence using the Caenorhabditis elegans infection model. We report that a combination of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 59 publications
(107 reference statements)
7
112
1
3
Order By: Relevance
“…Waters et al (67) demonstrated that AS directly binds LTA in vitro but LTA is not sufficient for bacterial aggregation. A more complex scenario, in which PrgB mediates interactions with extracellular DNA to enhance aggregation, was recently proposed by Bhatty et al (68). Our findings suggest that EpaI contributes to the formation of EBS, implying that the Epa polysaccharide may be a component of EBS.…”
Section: Figsupporting
confidence: 51%
“…Waters et al (67) demonstrated that AS directly binds LTA in vitro but LTA is not sufficient for bacterial aggregation. A more complex scenario, in which PrgB mediates interactions with extracellular DNA to enhance aggregation, was recently proposed by Bhatty et al (68). Our findings suggest that EpaI contributes to the formation of EBS, implying that the Epa polysaccharide may be a component of EBS.…”
Section: Figsupporting
confidence: 51%
“…PrgA could play a role in PrgB processing and form an adhesion complex with PrgB [18]. Furthermore, the same authors showed that other proteins (the cell-wall hydrolase and the VirB4-like ATPase) encoded by the plasmid could also play a role in biofilm formation [18]. …”
Section: Discussionmentioning
confidence: 96%
“…ICE_515_tRNA Lys , which also encodes a new CAMP factor conferring hemolytic properties recently reported that co-synthesis of PrgA and PrgB of pCF10 is required for robust biofilm development [18]. PrgA could play a role in PrgB processing and form an adhesion complex with PrgB [18].…”
Section: Discussionmentioning
confidence: 98%
“…As demonstrated above, in the presence of the coresident gene for the PrgX negative regulator, the P Q promoter is tightly repressed, responds to nanogram-per-milliliter concentrations of the innocuous cCF10 peptide pheromone, and has a large expression range over a fairly narrow inducer concentration range (roughly 1 to 20 ng of cCF10 per ml). While the experiments reported here all employed M9YEG medium, cCF10 pheromone-inducible heterologous gene expression also can be used in more complex media such as brain heart infusion or tryptic soy broth, with appropriate adjustments of inducing concentrations of cCF10 (33). Adjustments may also be required for induction under conditions other than exponential phase.…”
Section: Discussionmentioning
confidence: 99%